Ekorozwój jedyną drogą polskiej wsi i rolnictwa - Mieczysław Górny (Studia Ecologiae et Bioethicae)
Limiting agricultural production with the use of industrial methods is in society's best interest. Industrial farms are places where the natural degradation of soil, rural landscapes, and ground waters takes place. They are also places where farm animals are mistreated and suffer. The crops, being high are, at the same time, of low quality, posing threat to people's and animals' health. The only agricultural managing system which complies with the idea of eco-development is ecological farming, whose initiators were: Dezydery Chłapowski at the beginning of the 9th century, officer, Napoleon's aide-de-camp as well as Rudolf Steiner from Austria, philosopher, theologian, and occultist at the beginning of the 20th century. Neither of them had agricultural education, both were active in the area now belonging to Poland (in Turew in Wielkopolska district and in Kobierzyce near Wroclaw respectively). Ecological farming based on family farms is a combination of ethical, ecological, and economic approaches. Not only does it provide the highest quality food and feeding stuff but it also helps protect the environment, fertilizes the soil, caters to good growth conditions of cultivated plants and animals, provides new jobs, and improves living conditions in rural areas.